Pengembangan sumber daya ekonomi lokal di Kabupaten Sumenep: pendorong dan penghambat - Rozikin, Mochammad; Haris, Rillia Aisyah (Publisia: Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this study is to identify and analyze the drivers and restraining factors of the development of local economic resources. This study uses force field analysis to analyze the various forces / factors that affect a change, determine the source of its strength, and develop strategies to strengthen the drivers and weaken the inhibitors. The results showed that there were a number of driving factors, namely: 1) superior commodities; 2) Rules / policies; 3) Budget allocation; 4) Human resources availability; 5) Leadership. The restraining factors are: 1) Lack of coordination and collaboration of stakeholders involved; 2) The quality of human resources of farmers is still low; 3) community participation is still low; 4) Availability of infrastructure; 5) Commitment of stakeholders involved. This research is expected to be a material consideration for developing strategies to achieve success in developing local economic resources and providing recommendations to local governments to implement planned changes to be able to increase the added value and welfare of local communities.